The Novel is Only a Game or The French Lieutenant’s Woman as a Piece of Postmodernist Fiction - Alina Mirela Pascu (Berpusi Publishing, 2023)
Postmodernism is a multifaceted phenomenon of the mid to late 20th century, ubiquitous, ambiguous, paradoxical, fluid, double-coded (cultural) that simultaneously shows intellectual assimilation and mass culture, is also a continuation, disposal, and even succession of Modernism. This tripartite construction is an umbrella term related to several things at once, as it “left its mark in every cultural discipline from architecture to zoology, following the ways of biology, forestry, geography, history, law, literature and art in general. , medicine, politics, philosophy, sexuality, and so on. Yet these formless objects are still ghostly, and to some people, terrifying. Postmodern research methodology is an approach to research that emphasizes understanding of the complexity and diversity of social reality as well as the diversity of viewpoints and interpretations. Postmodern research suggests that the deployment of this